2012 15th International Conference on Computer and Information Technology (ICCIT) 2012
DOI: 10.1109/iccitechn.2012.6509735
|View full text |Cite
|
Sign up to set email alerts
|

A high embedding capacity image steganography using stream builder and parity checker

Abstract: Steganography is one of the arts and sciences of securing or hiding secret information in some cover media. In the present study, a new steganography technique is developed to hide large data in Bitmap image using stream builder and parity checker. This method uses the concept of odd and even parity for embedding and extracting of secret message. This method is an improvement of Least Significant Bit (LSB) method for hiding information in images. The proposed method can hide large data in a single Bitmap image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…When a user edits a wishlist item, the stock of the item could be updated, and how many of the item the user wants is also constantly modified. As a result, these two pieces of information are asynchronous, requiring real-time updates, and thus, a StreamBuilder, shown in Figure 5, is implemented [12]. The StreamBuilder widget treats these real-time data as streams, and since these data are stored in Firebase, it takes a stream that constantly requests a snapshot of the user's wishlist in the Firebase.…”
Section: Solutionmentioning
confidence: 99%
“…When a user edits a wishlist item, the stock of the item could be updated, and how many of the item the user wants is also constantly modified. As a result, these two pieces of information are asynchronous, requiring real-time updates, and thus, a StreamBuilder, shown in Figure 5, is implemented [12]. The StreamBuilder widget treats these real-time data as streams, and since these data are stored in Firebase, it takes a stream that constantly requests a snapshot of the user's wishlist in the Firebase.…”
Section: Solutionmentioning
confidence: 99%
“…It is observed that efficiency of the approach is highly attributed to the number of eligible pixels, with the moderate number of eligible pixels producing better results. On the other hand, Islam [11] used 24-bit bitmap image for embedding messages using stream builder and parity concept. One stream is built by aggregating LSBs of 8 bytes of pixels and then parity values of these pixels decide how the message will be embedded.…”
Section: Related Workmentioning
confidence: 99%
“…From the Table 6, it is observed that our proposed approach is able to produce better capacity and PSNR value compared to approaches introduced by Mandal and Das [19], Lin, et. al., [30] and Islam [11]. Moreover, although methods proposed by Wu, et.…”
Section: Comparison With the State-of-the-artsmentioning
confidence: 99%
“…For this above reason Steganography is more reliable than Cryptography. Figure-1 shows the main categories of file formats that can be used for Steganography [5]. Almost all digital file formats can be used for Steganography.…”
Section: Introductionmentioning
confidence: 99%